Antimicrobial susceptibility testing of Arcobacter butzleri and Arcobacter cryaerophilus isolated from buffalo milk with subclinical mastitis: A different approach - Altan, Feray; Yesilmen Alp, Simten (Journal of the Hellenic Veterinary Medical Society, 2022)
The aim of our study was the minimum inhibitory concentrations (MICs) of 9 antimicrobials in current use and 3 potentially new alternatives against Arcobacter spp. isolated from dairy buffaloes with subclinical mastitis, and to evaluate these parameters together with pharmacokinetic parameters. The Arcobacter isolates was isolated from milk samples collected from dairy buffaloes with subclinical mastitis. The susceptibility of Arcobacter strains to antimicrobials were determined with the NCCLS microdilution technique and, not seen the blur according to the recommendations at the lowest concentration of antibiotic. MIC value of vancomycin, erythromycin and tetracycline were not determined, and MIC value of ceftiofur, spiramycin and gentamicin have showed wide variations for isolated strains. However, cefquinome, tylosin, enrofloxacin and florfenicol were determined the best-performing agents against these strains. Antibiotics show concentration and time dependent killing, and studies have demonstrated the AUC/MIC, Cmax/MIC and t MIC ratios to be the best diviner of antibacterial effect. In the present study, based on the MIC values determined for selected antimicrobial agents, and pharmacokinetic parameters, amoxicillin, ceftiofur, cefquinome, enrofloxacin and florfenicol may be appropriate for the treatment of mastitis infections caused by susceptible Arcobacter spp. in buffaloes.